Respuesta :

Answer:

3x + y = -3

Step-by-step explanation:

Here ya go

Ver imagen calderonj4588
The standard form of linear equation is Ax + By = C, where A and B are ≠ 0, and A is positive.

Start by distributing -3 into the parenthesis:

y + 6 = -3(x + 1)

y + 6 = -3x - 1

Subtract 6 from both sides:

y + 6 - 6 = -3x - 1 - 6

y = -3x - 7

Then, add 3x to both sides:

3x + y = -7 ( This is the standard equation where a = 3, b = 1, and c = -7.)

Please mark my answers as the Brainliest, if you find this helpful :)